2009
DOI: 10.1007/s00125-009-1401-0
|View full text |Cite
|
Sign up to set email alerts
|

Circulating endothelial progenitor cells, endothelial function, carotid intima–media thickness and circulating markers of endothelial dysfunction in people with type 1 diabetes without macrovascular disease or microalbuminuria

Abstract: Aims/hypothesis Type 1 diabetes is associated with premature arterial disease. Bone-marrow derived, circulating endothelial progenitor cells (EPCs) are believed to contribute to endothelial repair. The hypothesis tested was that circulating EPCs are reduced in young people with type 1 diabetes without vascular injury and that this is associated with impaired endothelial function and increased carotid intima-media thickness (CIMT). Methods We compared 74 people with type 1 diabetes with 80 healthy controls. CD3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
101
3
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(125 citation statements)
references
References 51 publications
(62 reference statements)
13
101
3
3
Order By: Relevance
“…sICAM-1 was significantly higher in diabetics compared to control subjects but there wasn't any difference between diabetic subgroups. In the study of Sibal and cols., sICAM1 was significantly higher in T1DM patients compared to controls supporting our results (24). Bruno and cols.…”
Section: Biochemical and Clinic Markers Of Ed In T1dmsupporting
confidence: 90%
See 1 more Smart Citation
“…sICAM-1 was significantly higher in diabetics compared to control subjects but there wasn't any difference between diabetic subgroups. In the study of Sibal and cols., sICAM1 was significantly higher in T1DM patients compared to controls supporting our results (24). Bruno and cols.…”
Section: Biochemical and Clinic Markers Of Ed In T1dmsupporting
confidence: 90%
“…This hypothesis is supported by Sibal and cols. who demonstrated that FMD was reduced by % 45 in patients with T1DM without any complications compared to controls (24). Endothelin-1 is a marker of ED and plays role in angiogenesis, fibrosis, inflammation and acts as a vasopressor agent causing HT (25).…”
Section: Biochemical and Clinic Markers Of Ed In T1dmmentioning
confidence: 97%
“…Other than ex vivo cultivation of (purified) blood samples, flow-cytometric analysis of multilabeled blood samples has become a method of choice. 32,[43][44][45][46][47] Detecting untouched EPCs within the in vivo situation ideally in the progeny status with initial EC features is the basic idea of choosing flow cytometry. Among the various surface markers (Table), CD34 and KDR have turned out to be the most popular combination in humans (and Sca-1 and Flk-1, the murine homolog of KDR, in rodents).…”
Section: Separated Cd14mentioning
confidence: 99%
“…However before comparisons can be made between studies, it is important to consider the methods used to quantify EPC numbers in these studies. Circulating EPC numbers were quantified either by surface antigen expression on peripheral blood mononuclear cells (PBMNCs) (Brunner et al, 2009, Sibal et al, 2009, through the culture of early-outgrowth EPC colonies (Asnaghi et al, 2006) or through the uptake of acetylated LDL and binding of UEA-l to cultured PBMNCs (Loomans et al, 2004). To the best of our knowledge, there are currently no reports on the correlation between T1DM and the growth of late-outgrowth EPCs.…”
Section: Endothelial Progenitor Cells In Type 1 Diabetes Mellitusmentioning
confidence: 99%